A computational study on structure and stability of nitrogen-doped titanium clusters TinN (n = 1-10) - Ngoc Lan, Le Nguyen; Nam, Huynh Thanh; Cuong, Chau Hung; Trung, Nguyen Tien; Ngan, Vu Thi (Vietnam Journal of Chemistry, 2017)
A study was performed using density functional theory at the PW91PW91/DGDZVP2 level to investigate the structures and stability of the neutral nitrogen-doped titanium clusters TinN (n = 1-10). The most stable isomers may have spin state ranging from doublet to quartet to sextet. Interestingly, the ground-state structures of these clusters are consistently formed by adding an N atom on an edge and a face of the pure titanium cluster and the N atom prefers to stay on surface of the clusters. Doping with an N atom increases the stability of titanium clusters and decreases their metallicity. Moreover, the analyses of average binding energy, second-order energy differences and fragmentation energy according to cluster size imply a special stability of Ti6N. Keywords. N-doped titanium clusters, PW91PW91 functional, cluster stability, electronic structure, HOMO‑LUMO gap.